Writing Feeds Literature - Abdelhak NEMOUCHI (Revue des Sciences Humaines)
The place of writing in any training syllabus at all educational levels is essential. As all other language skills, writing has proved to be the cornerstone in the complex process of learning a language. The requirements for all subjects constituting the curriculum to be evaluated in the written form make the mastery of writingindispensable and the knowledge of its rules a perquisite for learning and success. In the English language more than in Arabic and French which prevail in the Algerian school, the rules which govern the paragraph appear as numerous and rigid, and often influence negatively on the students outcome in the subjects of literature, linguistics, civilisation and whatsoever. This situation has motivated the modest study at hand which aims to measure and compare the freshmen and sophomores’ students’ proficiency in writing and literature. The procedure consisted in collecting their marks in writing and comparing them to those obtained in literature. The comparative analysis revealed that the students’ marks in writing and literature reflect a logical correspondence between the learners’ performance in both modules. In other words, good students in writing are dominantly good in literature, and this is quite understandable because writing in literature class does not require any type of gift; it is simply a meticulous practice of the teachers’ instructions with negligible reference to creativity which is the basic substance of literature.